Analisis Kebangkrutan Pada Perusahaan Sektor Pariwisata, Restoran, dan Hotel - Nenny Syahrenny (Politeknik Negeri Jember, 2023)
The purpose was to test the bankruptcy potential and accuracy of the three models used to analyze company insolvency using the Altman Z-Score, Springate S-Score, and Zmijewski X-Score methods. Each model is calculated using ratio analysis of the elements of assets, liabilities, equity, and retained earnings. This study used secondary data that had been processed. The samples are tourism, restaurant and hotel companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. Using the purposive sampling method, predetermined criteria so that 26 companies with a total of 130 data. The analysis technique is to calculate financial ratios, then compare the results of the three bankruptcy prediction models and test their accuracy. As a result, the Springate S-Score model with the highest accuracy of 80.77% is considered more accurate in predicting the possibility of bankruptcy which supported by the existence of companies suspended by the IDX due to going concern issues.